The Validity of the “Lingga Batik Introduction” E-Module Developed Using the ADDIE Model for Cultural Arts Learning with Local Wisdom Content - Feby Sarianty; Dody Irawan; Nevrita; Zaitun (Raja Zulkarnain Education Foundation, 2025)
This study aims to examine the validity level of the “Pengenalan Batik Lingga” e-module, developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model in cultural arts learning based on local wisdom. The e-module was designed as an interactive digital medium incorporating Malay cultural values of the Riau Islands, particularly Lingga Batik motifs. The research employed a Research and Development (R&D) approach, with validations conducted by three experts: material, media, and language experts. The results showed significant improvements between the first and second validation stages. The average expert validation scores increased from 2.38 (not appropriate) to 4.25 (highly appropriate) for content, 2.28 to 4.00 for media, and 2.26 to 4.00 for language. The overall average increase of 77.5% indicates that the e-module meets the criteria of high validity and feasibility for instructional use. These findings reinforce the importance of developing digital learning media rooted in local culture to enhance learning relevance and motivation in the digital era.